Direct comparison of ferroelectric properties in Hf0.5Zr0.5O2 between thermal and plasma-enhanced atomic layer deposition. (5th October 2020) - Hur, Jae; Tasneem, Nujhat; Choe, Gihun; Wang, Panni; Wang, Zheng; Khan, Asif Islam; Yu, Shimeng
Abstract: Since the discovery of ferroelectricity in doped/alloyed HfO2 and ZrO2 thin film, many device engineers have been attracted to its sustainable ferroelectricity at the thickness of a few nanometer. While most of the previous studies have mainly focused on the ferroelectric properties of the thermally atomic layer deposited (THALD) Hf0.5 Zr0.5 O2 (HZO), the plasma-enhanced ALD (PEALD) HZO has not received much attention. In this work, a direct comparison between the two types of HZO thin films is carried out, where we found that a tradeoff exists between these two fabrication methods. While the THALD HZO was able to maintain a higher cycling endurance, the PEALD HZO showed more stable characteristics over the cycling with reduced wake-up and fatigue effects, in addition to better tolerance against breakdown under high electric field. Furthermore, the PEALD HZO could be crystallized with post deposition annealing at 350 °C, which is of great interest for the back-end-of-line compatibility with silicon fabrication processes.